An introduction to clinical emergency medicine - Garmel, Gus. M.; Mahadevan, Swaminatha V. (Cambridge University Press, 2012)
"The Practitioner's understanding of emergency medicine principles and practice, directly benefiting patient care in a variety of emergency settings An Introduction to Clinical Emergency Medicine, Second Edition is a much-needed resource for individuals practicing this challenging field. This textbook is novel in its approach to emergency medicine topics. It describes in detail the best and most current methods to care for patients in the emergency department, including initial evaluation, generation of differential diagnoses, problem solving, and management of challenging conditions based on presenting symptoms. Unlike other textbooks, in which the diagnosis is known, this textbook approaches clinical problems as clinicians manage patients - without full knowledge of the final diagnosis. It provides an understanding for how to approach patients with undifferentiated conditions, ask the right questions, gather historical data, utilize physical examination skills, and order and interpret appropriate laboratory and radiographic tests. This textbook also provides current management and disposition strategies with controversies presented, including pearls, pitfalls, and myths for topics covered. Chapters are written by nationally- and internationally respected clinicians, educators, and researchers in the field of emergency medicine. Second Edition of An Introduction to Clinical Emergency Medicine offers just the right combination of text, clinical images, and practical information for students, residents, physician assistants, nurse practitioners, and experienced physicians in all medical disciplines"--Provided by publisher.